Design of ring oscillator structures for measuring isolated NBTI and PBTI - Kim, Tony Tae-Hyoung (2013)
Ring oscillator based test structures that can separately measure the NBTI and PBTI degradation effects in digital circuits are presented for high-k metal-gate devices. The proposed test structures enable simultaneous stress of all devices under test in either NBTI or PBTI mode and measure frequency or threshold voltage shifts. The mathematical derivation also shows that the structure for frequency degradation measurement can directly be used for estimating the portion of the NBTI and PBTI in the conventional ring oscillator. The proposed test structures including beat frequency sensing circuitry have been designed in a 0.9V, 45nm SOI technology.